The design and application of a maximum arm resistance test for par terre defense in Iraqi national senior team greco roman wrestlers - Uldeen, A. S.; Burhan, W. Y.; Ismail, H. H.; Al-Sharbaji, N. H. (International Journal of Wrestling Science, 2022)
There is no doubt that every sports game has characteristics that characterize it and goals that it works to achieve through training, testing and measurement to achieve these goals. The fact that the sport of wrestling requires a great effort that does not stop when learning its tactics.